Corporate governance in Latin America - Alberto Chong; Florencio López-de-Silanes (Inter-American Development Bank, Research Department, 2007)
This paper analyzes recent trends of Latin America's institutional development regarding investor protection. In spite of the underdevelopment of the region's financial markets, there is slow movement towards legal reforms intended to protect investors and make regional markets more attractive to investors; current inadequacies in the region's legal institution's generate high levels of ownership concentration, poor access to external equity financing, and narrow equity markets. The evidence in this paper, based on firm-level data for six countries, shows that, like legal protection of investors, appropriate firm-level corporate governance is linked to lower costs for capital, better valuation, performance, and dividend payments across countries. Firms can compensate for their countries' legal deficiencies by distinguishing themselves through improved corporate governance practices, thus increasing transparency and limiting potential conflict between large and minority shareholders. Firms can additionally look for capital by issuing ADRs, as they have in recent years, although this practice undermines local capital markets. In the end, firms and regulators must improve their governance structures and shareholder protections if they are to meet the improved benchmarks of developed nations brought about by Asian, European, and U.S. scandals in recent years.
Keywords: G32; L22; 330; Corporate governance; Investor protection; Corporate valuation; Corporate Governance; Direktinvestition; Anlegerschutz; Finanzmarkt; Unternehmenswert; Lateinamerika